Inhibition of Integrin αVβ3 Signaling Improves the Antineoplastic Effect of Bexarotene in Cutaneous T-Cell Lymphoma - Cayrol, Maria Florencia (2022)
Bexarotene is a specific retinoid X receptor agonist that has been used for the treatment of cutaneous T-cell lymphoma (CTCL). Because bexarotene causes hypothyroidism, it requires the administration of levothyroxine. However, levothyroxine, in addition to its ubiquitous nuclear receptors, can activate the αVβ3 integrin that is overexpressed in CTCL, potentially interfering the antineoplastic effect of bexarotene. We thus investigated the biological effect of levothyroxine in relation to bexarotene treatment. Although in isolated CTCL cells levothyroxine decreased, in an αVβ3-dependent manner, the antineoplastic effect of bexarotene, levothyroxine supplementation in preclinical models was necessary to avoid suppression of lymphoma immunity. Accordingly, selective genetic and pharmacologic inhibition of integrin αVβ3 improved the antineoplastic effect of bexarotene plus levothyroxine replacement while maintaining lymphoma immunity. Our results provide a mechanistic rationale for clinical testing of integrin αVβ3 inhibitors as part of CTCL regimens based on bexarotene administration.